Optimizing Slack Resource Allocation: An Economic Approach to Sustainable Competitive Advantage - Lu-Yao Zhang; Xing-Can Zhang; Seong-Jin Choi (SAGE Open)
This study explores how slack resources can enhance firms’ sustainable competitive advantage by combining economics and organizational behavior within a strategic management framework. Specifically, we examine the relationships between three types of slack resources—available, recoverable, and potential—and three environmental dimensions: munificence, dynamism, and complexity. Our dataset comprises 34,261 observations from 4,045 listed firms across 34 provincial-level administrative regions in China, spanning the years 1993 to 2021. The results indicate that each type of slack resource has an inverted U-shaped relationship with performance, suggesting the existence of a Pareto optimal level of resource allocation. However, this relationship and the position of the Pareto optimal point are not constant. Environmental factors moderate the relationship between slack resources and performance, leading to fluctuations in Pareto optimal values and per-unit value. By expanding and integrating the resource-based view and the structure–conduct–performance paradigm, we explain the relationships between various slack resources and different industrial environments. Based on our findings, we provide suggestions for enhancing sustainable competitive advantage.